The making and legitimacy of the Ethiopian constitution: towards bridging the gap between constitutional design and constitutional practice - Regassa, Tsegaye (Afrika Focus, 2010)
This article describes the making of the 1995 constitution of the Federal Democratic Republic of Ethiopia (FDRE) and analyzes its implications for legitimacy. It contends that legitimacy of the constitution, which fosters delity to it, can –as one among other factors– help bridge the gap between constitutional design and constitutional practice. By making a process-content-context analysis of the constitution, it argues that the Ethiopian constitution which had a weak original legitimacy, can earn a derivative legitimacy through aggressive implementation. Aggressive imple- mentation, it is maintained, demands fidelity to the constitution. Fidelity and other components of a redemptive constitutional practice (such as creative constitutional interpretation, constitutionally informed legislation, positive constitutional amendment, and constitutionally responsible voting) help deal with the perennial question of how to bridge the gap between constitutional design and constitutional practice in Ethiopia and beyond. Key words: Ethiopia, making of constitutions, constitutional legitimacy, fidelity to constitutions, constitutional redemption